Views of nurses and other healthcare workers on interventions to reduce disrespectful maternity care in rural health facilities in Kilifi and Kisii counties, Kenya: analysis of a qualitative interview study - Marleen Temmerman; Adelaide M Lusambili; Jerim Obure; Stefania Wisofschi; Lucy Nyaga; Kennedy Mulama (BMJ Open)
Objective There is an abundance of evidence illuminating the factors that contribute to disrespectful maternity care in sub-Saharan Africa. However, there is limited documented evidence on how some of the key influences on the mistreatment of women could be addressed. We aimed to document the perspectives of nurses and other healthcare workers on existing and potential strategies embedded at the health facility level to promote respectful delivery of healthcare for women during delivery and on what interventions are needed to promote respectful and equitable treatment of women receiving maternity care in rural Kenya.Design, setting and participants We analysed relevant data from a qualitative study based on in-depth interviews with 24 healthcare workers conducted between January and March 2020, at health facilities in rural Kilifi and Kisii counties, Kenya. The facilities had participated in a project (AQCESS) to reduce maternal and child mortality and morbidity by improving the availability and the use of essential reproductive maternal and neonatal child health services. The participants were mostly nurses but included five non-nurse healthcare workers. We analysed data using NVivo V.12, guided by a reflective thematic analysis approach.Results Healthcare workers identified four interconnected areas that were associated with improving respectful delivery of care to women and their newborns. These include continuous training on the components of respectful maternity care through mentorships, seminars and organised training; gender-responsive services and workspaces; improved staffing levels; and adequate equipment and supplies for care.Conclusions These findings demonstrate some of the solutions, from the perspectives of healthcare workers, that could be implemented to improve the care that women receive during pregnancy, labour and delivery. The issues raised by healthcare workers are common in sub-Saharan African countries, indicating the need to create awareness at the policy level to highlight the challenges identified, potential solutions, and application or implementation in different contexts.